Comparison Between Nested-PCR and ELISA for the Detection of Toxoplasmagondii in Blood and Milk and its Genotyping in Lactating Goats and Aborted Women in Iraq - H Madi, Entesar; R Al-Samarai, Firas; M Maaen, Yusuf; K Gangwar, Shishir (The Iraqi Journal of Veterinary Medicine, 2022)
The present study aimed to assess enzyme-linked immunosorbent assay (ELISA) and nested-polymerase chain reaction (n-PCR) methods based on B1 gene for the detection of Toxoplasma (T.) gondii in the blood and milk of local Iraqi goats. The SAG3 gene was also used to identify the genotyping of T. gondii in goats and aborted women in Iraq. A total of 240 (80 blood, 80 sera, 80 milk) lactating goats and 30 blood samples from aborted women were included in this study. A total of 17 (21.2%) infected goats were found in blood samples and 23 (28.7%)in milk samples when using n-PCR, while the numbers were 23 (28.7%) and 17 (21.2%) when using ELISA. Aborted women had an overall infection rate of 50% when using ELISA and 33% when using n-PCR. The degree of agreement between n-PCR in milk and blood was almost perfect (Kappa=0.801), with a sensitivity of 100 and a specificity of 90.5, while there was a slight degree of agreement (Kappa=0.14) between n-PCR and ELISA in blood, with 58.8 sensitivity and 74.6 specificity. The results of the comparison between nPCR in blood and ELISA in milk showed positive samples of 17 (21.2%) for each, with 82.4sensitivity and 22.2 specificity, and no agreement (Kappa=–0.046). Sequencing of the SAG3gene of T. gondii from goat and human isolates showed that the similarity ranged from 98.65–99.90% for genotypes I and III. In conclusion, n-PCR may be more accurate than ELISA for detecting T. gondii in blood and milk. In addition, the phylogenetic tree's evidence of a high degree of similarity between human and goat isolates provides further evidence